Role of the notched unipolar electrogram in guiding catheter ablation of frequent premature ventricular contractions originating from the ventricular outflow tract. Issue 12 (December 2020) - Huang, Li-Hong; Gao, Ming-Yang; Zeng, Li-Jun; Xie, Bo-Qia; Shi, Liang; Wang, Yan-Jiang; Yin, Xian-Dong; Wang, Yu-Xing; Liu, Xiao-Qing; Tian, Ying; Yang, Xin-Chun; Liu, Xing-Peng
Objective: To investigate the value of a notched unipolar electrogram (N-uniEGM) in confirming the origin of premature ventricular contractions originating from the ventricular outflow tract (VOT-PVC) during mapping and ablation procedures. Methods: This retrospective study enrolled consecutive patients with symptomatic idiopathic frequent VOT-PVCs that underwent radiofrequency ablation. The characteristics of the uniEGM of the successful ablation targets were analysed. N-uniEGM was defined as the uniEGM presenting a QS morphology with ≥1 steep notches on the downstroke deflection. All patients were followed-up for 3 months post-ablation. Results: The study enrolled 190 patients with a mean ± SD age of 49.0 ± 15.3 years. N-uniEGMs were recorded in 124 of 190 (65.3%) patients. The N-uniEGM distribution area was limited to a mean ± SD of 0.8 ± 0.4 cm 2 . N-uniEGM showed consistency with the outcomes of activation mapping and pace mapping. Patients with an N-uniEGM had an ablation success rate of 98.4% (122 of 124) and their ablation times were significantly shorter than those without an N-uniEGM (7.6 ± 3.8 s versus 15.8 ± 8.8 s, respectively). The sensitivity and specificity of N-uniEGM in predicting successful ablation of VOT-PVCs were 72.6% and 91.7%, respectively. Conclusion: N-uniEGM was a highly specific and moderately sensitive predictor of successful radiofrequency ablation in patients with VOT-PVCs.